Analysis of Barriers, Challenges and Strategies in Teaching Indonesian Language Subjects in Elementary Classes at SDN 060853 - Fitri, Fitri; Sinaga, Dearni; Monica, Elia; Hutauruk, Godlin; Haloho, Jelita; Tasya, Rani; Gagarin, Tesalonika (CV. Rayyan Dwi Bharata, 2024)
Research on the analysis of barriers, challenges and strategies in teaching Indonesian language subjects in low grades needs to be done, because there are many barriers, challenges and strategies that need to be known and faced at this time. This type of research is descriptive qualitative. The subjects in this study were grade 1, 2 and 3 teachers at SD Negeri 060853. Data collection techniques used observation, interviews, and documentation. The results showed several obstacles that are often faced by teachers, such as low teaching skills, limited facilities and infrastructure, and lack of innovative learning methods. One solution that can be applied is to improve teachers' teaching skills through training and workshops that focus on developing active and innovative learning methods. And teachers create an interactive and interesting learning atmosphere for students.